Streamlining mobile banking into loan repayment system for microfinance institutions / Afifa Malina Amran … [et al.] - Amran, Afifa Malina; Mohamed, Intan salwani; Syed Yusuf, Sharifah Norzehan; Rozzani, Nabilah (Universiti Teknologi MARA Cawangan Selangor, 2019)
The competitive environment of microfinance industry has indeed forced microfinance institutions (MFIs) to balance their dual goals of outreach and sustainability. Based on this, the focus of this current research is placed on its objective to study how the implementation of mobile banking would be better to streamline the accounting information system for MFIs, specifically with regards to loan repayments. To better understand the current practice of mobile banking in IMFIs, this study was conducted using a qualitative case study on Amanah Ikhtiar Malaysia (AIM), one of the biggest MFIs in Malaysia. It was found from the study that the usage of mobile banking can streamline AIM’s loan repayment system and increases its productivity by having shorter meeting times with recipients. Findings from this study shed lights on the critical role of accounting information system to adapt with applications of new technology, which could also be relevant for other organisations in various financial sectors. This study has highlighted the role of accounting information system in MFIs, especially with regards to its loan repayment system. As such, practitioners will be able to consider whether the lessons learnt from this case study can help them to solve similar issues within the context of their organisation. Findings from this study has significantly contributed to the microfinance industry by focusing on the role of mobile banking to improve loan repayment system in MFIs for service enhancement, hence becoming model institutions which practice modern accounting techniques through the usage of technology.